Dental caries associated with dietary and toothbrushing habits of 6- to 12-year-old mentally retarded children in Taiwan - Hsiu-Yueh Liu; Shun-Te Huang; Szu-Yu Hsuao; Chun-Chih Chen; Wen-Chia Hu; Ya-Yin Yen (Elsevier, 2009)
In this study, we analyzed the influence of dietary factors and toothbrushing habits on dental caries in children with mental retardation (MR). Materials and methods: In total, 168 children with MR, aged 6-12 years, were selected from a large cross-sectional survey entitled "Oral health survey and oral hygiene education for the disabled in Taiwan", which used a stratified cluster sampling design and probability proportional to size for sampling. Oral examinations were carried out by dentists, who were trained such that the kappa score of their interexaminer agreement exceeded 0.8. Data on demographics, diet and toothbrushing habits were collected using a standardized questionnaire completed by a parent or caregiver. A database was designed using Microsoft Access, and the data were analyzed with SAS and JMP software. Results: The number of permanent decayed teeth, DMFT index, and caries prevalence of 6-year-old children (0.25, 0.25, and 18.75%, respectively) significantly increased with age to 12 years old (2.37, 3.54, and 72.88%, respectively) (P < 0.05), and this effect was reversed in the primary dentition. Children with a habit of asking for sweets, children who ate sweets at least once a day, children who received sweets as a reward for behavior control, and children who usually held food in their mouth had a higher number of decayed teeth in their primary dentition. Children who had a higher number of decayed teeth and deft index tended to have a poor appetite, eat soft foods such as porridge, and spend a long time eating. Children who needed help cleaning their teeth comprised 39.62% of the cohort. Children who did not clean their teeth regularly had the highest number of decayed teeth at 2.38. Conclusion: Children with MR tend to have poor oral health. A higher number of decayed teeth and a higher prevalence of caries were statistically significantly related to eating sweets and not having good oral hygiene habits of toothbrushing after eating.